2009
DOI: 10.3109/10903120903349788
|View full text |Cite
|
Sign up to set email alerts
|

Air Versus Ground Transport of the Major Trauma Patient: A Natural Experiment

Abstract: This unique natural experiment led to better matched air vs. ground cohorts for comparison. As per TRISS analysis, air transport of the adult major trauma patient is associated with significantly improved survival as compared with ground transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 24 publications
(26 reference statements)
0
28
0
2
Order By: Relevance
“…Despite a paucity of reported objective data, air ambulance services in numerous countries have been shown to improve patient outcomes when compared with ground transport in select circumstances. [1][2][3] These benefits have not, however, been noted in all studies, and the value of air ambulance transport continues to be debated.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a paucity of reported objective data, air ambulance services in numerous countries have been shown to improve patient outcomes when compared with ground transport in select circumstances. [1][2][3] These benefits have not, however, been noted in all studies, and the value of air ambulance transport continues to be debated.…”
Section: Discussionmentioning
confidence: 99%
“…29 Fourth, HEMS is sometimes used in areas of sparse ground EMS availability in which a ground transport to the trauma center may leave a community without EMS coverage for an extended period of time. 11 Studies have shown improved outcomes with HEMS transport, [30][31][32][33][34] finding as much as a 52% reduction in mortality 8 and saving as much as one to 12 lives per 100 uses of HEMS. 35 Many studies have shown no such improvement.…”
Section: Discussionmentioning
confidence: 99%
“…13 Traditional EMS performance measures have focused on response times, [14][15][16][17][18] appropriate patient selection for prehospital rapidsequence intubation (RSI) 19 and air versus ground transportation, 20 and out-of-hospital cardiac arrest survival. 21,22 Newer efforts are expanding EMS benchmarks for various clinical entities encountered by EMS systems, such as ST-segment elevation myocardial infarction (STEMI), [23][24][25] acute stroke, 26 pulmonary edema, asthma, and seizures.…”
Section: Development Of Performance Metricsmentioning
confidence: 99%